Optimizing Electronic Quality Factor toward High-Performance Ge1- x - y Tax Sby Te Thermoelectrics The Role of Transition Metal Doping - Li, Meng (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 Wiley-VCH GmbH.